Quantitative whole‐body magnetic resonance imaging in children with Pompe disease: Clinical tools to evaluate severity of muscle disease. Issue 1 (14th October 2020) - Fernandes, Samuela A.; Khan, Aleena A.; Boggs, Tracy; Bowling, Michael; Austin, Stephanie; Stefanescu, Mihaela; Case, Laura; Kishnani, Priya S.
Abstract: Objective: Since the introduction of enzyme replacement therapy (ERT) with alglucosidase alfa, there has been increased survival in patients with Pompe disease. It is essential to characterize and quantify the burden of disease in these patients. Here, we report a measure of muscle fat infiltration in children with infantile and pediatric late‐onset Pompe disease (IPD and LOPD, respectively) to better understand the extent of muscle involvement. Methods: Eleven pediatric patients with Pompe disease (five IPD, six LOPD), ages 7‐17 years, received whole‐body magnetic resonance imaging (WBMRI), muscle strength testing using the modified Medical Research Council (mMRC) scale, functional assessment using gait, stairs, gowers, chair (GSGC), and urine glucose tetrasaccharide (Glc4 ) testing. The intramuscular fat seen on WBMRI was quantified using proton density fat fraction (PDFF) and correlated to appropriate muscle strength and functional tests, and urine Glc4 . Results: Patients with IPD, although younger, had higher mean PDFF values than LOPD patients (11.61% vs 8.52%). Significant correlation existed between PDFF and the GSGC assessment ( r = .9273, P = .0003). Moderate correlation existed between PDFF and mMRC ( r = −.667, P = .0831), and PDFF and urine Glc4 ( r = .6121, P = .0667). Anterior tibialis was in the top quartile of muscle involvement for patients with LOPD. Conclusion: In the past, physical therapy assessments alone have been used to track disease progression. Here, we show the clinical utility of WBMRI in quantifying muscle involvement in children with Pompe disease, especially regarding the novel involvement of anterior tibialis in children with LOPD, to better assess baseline muscle burden and mapping disease progression in children treated with ERT.